Difficult Airway Management in Adult Coronavirus Disease 2019 Patients: Statement by the Society of Airway Management. (12th March 2021) - Foley, Lorraine J.; Urdaneta, Felipe; Berkow, Lauren; Aziz, Michael F.; Baker, Paul A.; Jagannathan, Narasimhan; Rosenblatt, William; Straker, Tracey M.; Wong, David T.; Hagberg, Carin A.
Abstract : The coronavirus disease 2019 (COVID-19) disease, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), often results in severe hypoxemia requiring airway management. Because SARS-CoV-2 virus is spread via respiratory droplets, bag-mask ventilation, intubation, and extubation may place health care workers (HCW) at risk. While existing recommendations address airway management in patients with COVID-19, no guidance exists specifically for difficult airway management. Some strategies normally recommended for difficult airway management may not be ideal in the setting of COVID-19 infection. To address this issue, the Society for Airway Management (SAM) created a task force to review existing literature and current practice guidelines for difficult airway management by the American Society of Anesthesiologists Task Force on Management of the Difficult Airway. The SAM task force created recommendations for the management of known or suspected difficult airway in the setting of known or suspected COVID-19 infection. The goal of the task force was to optimize successful airway management while minimizing exposure risk. Each member conducted a literature review on specific clinical practice section utilizing standard search engines (PubMed, Ovid, Google Scholar). Existing recommendations and evidence for difficult airway management in the COVID-19 context were developed. Each specific recommendation was discussed among task force members and modified until unanimously approved by all task force members. Elements of Appraisal of Guidelines Research and Evaluation (AGREE) Reporting Checklist for dissemination of clinical practice guidelines were utilized to develop this statement. Airway management in the COVID-19 patient increases HCW exposure risk. Difficult airway management often takes longer and may involve multiple procedures with aerosolization potential, and strict adherence to personal protective equipment (PPE) protocols is mandatory to reduce risk to providers. When a patient's airway risk assessment suggests that awake tracheal intubation is an appropriate choice of technique, and procedures that may cause increased aerosolization of secretions should be avoided. Optimal preoxygenation before induction with a tight seal facemask may be performed to reduce the risk of hypoxemia. Unless the patient is experiencing oxygen desaturation, positive pressure bag-mask ventilation after induction may be avoided to reduce aerosolization. For optimal intubating conditions, patients should be anesthetized with full muscle relaxation. Videolaryngoscopy is recommended as a first-line strategy for airway management. If emergent invasive airway access is indicated, then we recommend a surgical technique such as scalpel-bougie-tube, rather than an aerosolizing generating procedure, such as transtracheal jet ventilation. This statement represents recommendations by the SAM task force for the difficult airway management of adults with COVID-19 with the goal to optimize successful airway management while minimizing the risk of clinician exposure.